“QO’RQUV” KONSEPTINI IFODALOVCHI LEKSIK-SEMANTIK VOSITALARNING KLASSIFIKATSIYASI («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article deals with the significance of the lexical-semantic analysis of the lexical field denoting negative emotions, which has been one of the main topics in linguistics in recent years, and the detailed determination of its role and essence in its proper mastery.